Comparison Study of Phoenix dactylifera L. and Nerium oleander L. as Biomonitors for Lead and Other Elements - Al-Shayeb, S.M. (Asian Journal of Chemistry, 2012)
The ability of Phoenix dactylifera leaflets to retain heavy metal pollutants was compared with the leaves of Nerium oleander. Pair samples of the two species were collected from 15 sites with different degrees of metal pollution in Riyadh city. The metal content (Pb, Zn, Cu, Cr, Ni and Li) was determined for washed and unwashed samples. Both plant species seem to have a comparable ability to retain these elements on the unwashed leaves. However, N. oleander showed higher lead, zinc and copper levels in the washed leaves than P. dactylifera leaflets which could be attributed to their adsorption in leaf surfaces.